1990
DOI: 10.1111/j.1151-2916.1990.tb06753.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Chemical Influences of Silicate Grain‐Boundary Phases in Yttria‐Stabilized Zirconia

Abstract: The microstructure and chemistry of grain-boundary phases in silicate-doped YZO3-ZrO2 ceramics were evaluated by analytical electron microscopy. Two different silicate compositions were used: one an aluminosilicate and the other a horosilicate glass. These grain-boundary phases had a significant impact on the grain morphology, the chemical composition of the grains, and the crystallization of second phases. These results indicate that controlled additions of specific glass phases may provide a means for tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Based on a continuum approach incorporating interfacial energies, has claimed for the existence of a stable equilibrium thickness of these glassy phases in ceramics. Following these works, a number of authors [1][2][3]8 observed intergranular non-crystalline films in silica-doped zirconia, with a constant thickness at grain boundaries and the presence of vitreous silica pockets at multiple junctions. However, others 9-11 only found amorphous pockets of a silica-rich phase at multiple junctions, but not at grain boundaries.…”
Section: Introductionmentioning
confidence: 96%
“…Based on a continuum approach incorporating interfacial energies, has claimed for the existence of a stable equilibrium thickness of these glassy phases in ceramics. Following these works, a number of authors [1][2][3]8 observed intergranular non-crystalline films in silica-doped zirconia, with a constant thickness at grain boundaries and the presence of vitreous silica pockets at multiple junctions. However, others 9-11 only found amorphous pockets of a silica-rich phase at multiple junctions, but not at grain boundaries.…”
Section: Introductionmentioning
confidence: 96%
“…However, in 8Y-CSZ the addition of silica at the triple junctions allows this phase to act as a barrier to crack propagation so that the fracture toughness is increased [47]. Thus, the purity of the material is critical as other glassy phases are wetting at room temperature although pure SiO 2 is not wetting [22,30]. …”
Section: Discussionmentioning
confidence: 97%
“…In order to achieve the conditions required for superplastic deformation in Y-CSZ ceramics, it is essential both to suppress static grain growth during preliminary sintering and to limit the occurrence of dynamic grain growth at high temperatures. The presence of a second phase, or specifically an appropriate glassy intergranular phase with a low solubility for the ceramic cations and a high viscosity, may serve to promote superplasticity in zirconia ceramics by increasing the resistance to cavity nucleation and enhancing the occurrence of grain boundary sliding [20][21][22][23][24][25][26][27]. For example, the addition of SiO 2 to TZP extends the ductility during superplastic forming [28] and the addition of 5 wt% colloidal silica to cubic YSZ ceramics enhances superplastic-like flow in compression [29].…”
Section: Introductionmentioning
confidence: 99%
“…On upper side m-ZrO2 also appeared due to the t-ZrO2 → m-ZrO2 transformation. Lin et al 20 supposed that alumina silicate glasses in the grain boundaries can scavenge yttrium ions from t-ZrO2 grains, which is leading to a loss of stability of the tetragonal phase and t-ZrO2 → m-ZrO2 transformation can take place. In our case such transformation may also occur due to the presence of small glassy phase, even though we have not detected alumina silicate glass by XRD.…”
Section: Phase Compositionsmentioning
confidence: 99%